1992
DOI: 10.1016/0014-5793(92)80593-6
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 5,6‐dihydroxyeicosatetraenoic acids A novel pathway for lipoxin formation by human platelets

Abstract: Leukotriene A4 may be metabolized to 5(S),6(R)‐ and 5(S),6(S)‐dihydroxy‐7,9‐trans‐11,14‐cis‐eicosatetraenoic acids by enzymatic or non‐enzymatic hydrolysis. Incubation of human platelet suspensions with these dihydroxy acids led to the formation of lipoxin A4 and 6(S)‐lipoxin A4 via lipoxygenation at C‐15. Furthermore, human platelets converted the two 5(R),6(S)‐ and 5(R),6(R)‐dihydroxy‐7,9‐trans‐11,14‐cis‐eicosatetraenoic acids to tetraene‐containing trihydroxyeicosatetraenoic acids. In contrast, leukotrienes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…18,22 Given cellular conditions, the second major product of human and porcine h5-LOX is LTA 4 , 5962 which is unstable in water and easily hydrolyzed into various 5,6-diHETE epimers nonenzymatically or by epoxide hydrolase. 18,29 This is a minor pathway in the cell, however, with the main hydrolysis product being LTB 4 formed by LTA 4 hydrolase. 63,64 We demonstrated that h15-LOX-2 reacts with 5-HPETE, and considering that the locations of the hydroperoxy and epoxy moieties were far from the methyl end of 5,6-diHETE and LTA 4 , respectively, we suspected that h15-LOX-2 could generate LxA 4 from 5,6-diHETE and/or LTA 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…18,22 Given cellular conditions, the second major product of human and porcine h5-LOX is LTA 4 , 5962 which is unstable in water and easily hydrolyzed into various 5,6-diHETE epimers nonenzymatically or by epoxide hydrolase. 18,29 This is a minor pathway in the cell, however, with the main hydrolysis product being LTB 4 formed by LTA 4 hydrolase. 63,64 We demonstrated that h15-LOX-2 reacts with 5-HPETE, and considering that the locations of the hydroperoxy and epoxy moieties were far from the methyl end of 5,6-diHETE and LTA 4 , respectively, we suspected that h15-LOX-2 could generate LxA 4 from 5,6-diHETE and/or LTA 4 .…”
Section: Resultsmentioning
confidence: 99%
“…31,37–39 Yet another route can be initiated by h5-LOX’s major product, 5 S - trans -5,6-oxido-7 E ,9 E ,11 Z ,14 Z -eicosatetraenoic acid (LTA 4 ), which can then be converted into LxA 4 via hydroperoxidation by either h15-LOX-1 in reticulocytes or h12-LOX in platelets; hydrolysis of the epoxide nonenzymatically or by epoxide hydrolase and reduction by GP are needed to convert the resulting 15 S -hydroperoxy-LTA 4 into the final product LxA 4 . 18,22,27,28 Additionally, LTA 4 compounds that are not hydrolyzed to their main product (5 S ,12 R -dihydroxy-6 Z ,8 E ,10 E ,14 Z -eicosatetraenoic acid (LTB 4 )) can also be converted to 5 S ,6 R -dihydroxy-7 E ,9 E ,11 Z ,14 Z -eicosatetraenoic acid (5,6-diHETE) by soluble epoxide hydrolase or non-enzymatic hydrolysis to either 5 S ,6 R -diHETE or 5 S ,6 S -diHETE. 18,29,40,41 5 S ,6 R -diHETE can then react with h12-LOX to generate LxA 4 , while 5 S ,6 S -diHETE will generate 6 S -LxA 4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar, however, to the situation in the presence of exogenous substrate, where LXB 4 levels were too weak to be detected. 15-LO action on the small amounts of 5,6-diHETEs occurring from the nonen-zymatic LTA4 opening would be able to produce LXs in the same manner as platelets (40), but for the same reason, this mechanism would not be retained. Therefore, since 15(S)-HETE was not recovered, it was not biosynthesized or was rapidly catabolized by to hydroxylation or 13 oxidation, being thus undetectable nor able to lead to LXs.…”
mentioning
confidence: 99%